Relationship between vitamin D deficiency and serum ferritin level in healthy women - Mohanad Adel Mohammed; Mushtaq Talib Abed; Muhannad Shweash; Hayder Adnan Fawzi; Muntaha Qasim Hendi; Ashwaq Talib Duraij; Ghuran Mahdi Salih (International Journal of Research in Pharmaceutical Sciences, 2019)
Vitamin D is an essential vitamin that regulates many biological processes and involved in the ‎activity of many organs like the skin, bone, kidney, etc. ferritin is an essential marker for ‎assessment of anemic status. The current study aimed to assess the relationship between ferritin ‎and vitamin D3 in healthy women at various age groups. A cross-sectional study carried out in ‎Ramadi city and involved 92 healthy women aged from ‎20-50 years‎, the participants divided into two groups according to age: group I with age ‏ ‎20 – 35 years and group II with age 36 – 50 years. In the present study mean vitamin D3 in group II ‎11.8 ‎±‎ 3.5‎ ‎ng/dL was ‎significantly lower than group I (35.3 ‎±‎ 12.2‎ ng/dL) p-value < 0.001, a similar ‎finding observed for ferritin (‎19.6 ‎±‎ 13.9‎ ‎vs ‎66.7 ‎±‎ 52.1‎, p-value <0.001). There was a direct relationship between ferritin with vitamin D. However, this relationship was ‎only significant in group II (p-value <0.05), while in group I it was statistically significant. In conclusion, low vitamin D levels associated with low ferritin, indicating that vitamin D ‎deficiency is associated with anemia.